Nurses' expectations about the succession of leaders in the hospital context - Alyne Leite Gomes Nogueira; Denize Bouttelet Munari; Luana Cássia Miranda Ribeiro; Ana Lúcia Queiroz Bezerra; Lucieli Dias Pedreschi Chaves
Objective: to analyze the expectation of nurses about the succession of leaders in the hospital context. Method: a descriptive and exploratory study of a qualitative approach carried out with 36 nurses from a public university hospital selected using the snowball technique. The data collection was done through semi-structured interviews that were recorded and analyzed based on the assumptions of the Content Analysis technique, Thematic modality. Ethical criteria were adequately met. Results: the reports comprised two central categories, "Who Will Take My Place?" and "Potential and Openness to Plan the Succession of Leadership in Nursing," the latter being divided into two subcategories: "Nursing leadership in the hospital five years from now" and "Strengths for the implementation of a leadership succession plan". Conclusion: from the results, positive aspects of the diagnosis of the leadership profile in the institution that favor the development of succession planning were verified. In addition, it was possible to perceive the necessity of the development of this planning in the hospital and its importance for the succession of leadership in Nursing. In this context, this study presents itself with an innovative character for exposing a theme that aims to potentiate the future of Nursing.